Patterns of β diversity in aquatic ecosystems at different spatial and temporal scales. - Diniz, Leidiane Pereira (2021)
Species are heterogeneously distributed and environmental changes, such as the construction of dams or extreme climate events, can modify the dynamics of aquatic organisms. Understanding the processes that drive diversity, across long time periods, can help in the establishment of increasingly accurate conservation measures. This thesis evaluated the patterns of β diversity and metacommunity structure at different spatial and temporal scales in three independent studies in the Upper Paraná river floodplain, Brazil. The first analyzed the seasonal variation of zooplankton β and Elements of Metacommunity Structure [EMS] of zooplankton, over four years (two years of prolonged drought and two years of extreme flooding), and on a smaller (sub-basins) and a larger scale (floodplain). Regardless of the hydrological period and spatial scale, zooplanktonic metacommunity structure remained practically constant throughout the four years, with the predominance of the Clementsian pattern. The predominance of the Clementsian pattern suggests that the associations of zooplankton species in the floodplain responded similarly to the environmental gradient and that the responses differed among species groups. In the second, the taxonomic (LCBD-t) and functional (LCBD-f) ecological uniqueness of zooplankton over 19 years was determined in lakes and lotic systems of two sub-basins (dammed and free-flowing), in addition to investigating which processes (temporal, environmental and biological) drive LCBD-t and LCBD-f. Regardless of the characteristics of each sub-basin, the highest LCBD-t and LCBD-f were related to lower species and trait richness, respectively. The temporal processes were the main drivers of the ecological uniqueness of zooplankton, and they were more important than the biological processes (phytoplankton biovolume and fish biomass, representing food resource and potential predation, respectively). Finally, it was tested whether, in a dammed sub-basin, a prolonged drought makes aquatic metacommunities (phytoplankton, zooplankton, and fish) more similar over time than a period that includes extreme flood events. Only zooplankton underwent homogenization during this period. The β diversity of phytoplankton and fish did not change between different hydrological periods, indicating that the dispersion type (passive or active) does not interfere with drought homogenization. The response between the biological groups was different, reinforcing that the groups are not surrogates of each other. The greater β diversity in the period with extreme floods shows, at least for zooplankton, the importance of the flood pulse, reducing the negative effects of prolonged drought in a dammed sub-basin. The results showed the predominance of a metacommunity pattern resulting from high turnover (Clementsian), indicating that conservation measures should include a greater number of sites, including those with less richness, as they may have a different composition (> LCBD). We also emphasize the importance of considering different scales, as each can provide unique insights. It is important that biodiversity studies consider β diversity to understand the mechanisms that drive the metacommunity in the face of environmental changes, especially over longer time scales.